Feminism and the politics of identity in Ingrid de Kok’s Familiar Ground - Mashudu C. Mashige (Tydskrif vir Letterkunde, 2017)
Through an analysis of selected representative poems from Ingrid de Kok’s Familiar Ground, this article examines the role played by feminist poetry in the quest to address gender-related issues as well as to contribute constructively to South Africa’s liberation from patriarchal apartheid. The article further argues that feminist writers desire to (re)negotiate the space within which they can (re)construct and articulate their identities as women and mothers, and that in such a context the politics of identity cannot be detached from other aspects within the struggle for socio-political and economic emancipation. Thus characteristics of apartheid oppression are contrasted with the patriarchal domination opposed by feminist writers.